2022
DOI: 10.1186/s40249-022-00981-1
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging mathematical models of disease dynamics and machine learning to improve development of novel malaria interventions

Abstract: Background Substantial research is underway to develop next-generation interventions that address current malaria control challenges. As there is limited testing in their early development, it is difficult to predefine intervention properties such as efficacy that achieve target health goals, and therefore challenging to prioritize selection of novel candidate interventions. Here, we present a quantitative approach to guide intervention development using mathematical models of malaria dynamics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Our analysis then applied a mathematical framework for predicting determinants of intervention impact and defining minimum drug profile criteria. This framework has been previously described, 28 and was demonstrated in a proof-of-concept study 27 (as summarised in appendix 1.4). In brief, we used the individual-based malaria transmission model to simulate scenarios over a wide range of input values for intervention coverage and drug initial efficacy and duration of protection.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis then applied a mathematical framework for predicting determinants of intervention impact and defining minimum drug profile criteria. This framework has been previously described, 28 and was demonstrated in a proof-of-concept study 27 (as summarised in appendix 1.4). In brief, we used the individual-based malaria transmission model to simulate scenarios over a wide range of input values for intervention coverage and drug initial efficacy and duration of protection.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we trained an HGP ( Binois and Gramacy, 2021 ) on a limited set of OpenMalaria simulations (3500–11,500 simulations). We then used the trained emulator to predict the output of OpenMalaria for a large number of simulations and used these outputs to perform the global sensitivity analysis ( Figure 1C ), adapting a similar approach to Golumbeanu et al, 2022 and Reiker et al, 2021 . Our approach involved: (i) randomly sampling combinations of parameters; (ii) simulating and estimating the rate of spread of the resistant genotype for each parameter combination in OpenMalaria; (iii) training an HGP to learn the relationship between the input (for the different drivers) and output (the rate of spread) with iterative improvements to fitting through adaptive sampling; and (iv) performing a global sensitivity analysis based on the Sobol variance decomposition using the trained emulator ( Kilian et al, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…We trained the HGP on the training dataset using the function mleHetGPfrom the R package ‘hetGP’ ( Binois and Gramacy, 2021 ). We chose to use HGP as it was successfully used in two previous studies that performed global sensitivity analyses of OpenMalaria ( Reiker et al, 2021 ; Golumbeanu et al, 2022 ). In addition, Reiker et al, 2021 tested different emulators and found that HGP provided the best fit with a limited number of simulations (analysis not shown in the published study).…”
Section: Methodsmentioning
confidence: 99%
“…Modelling captures these dynamics to link individual and community benefits, allowing clinical trial evidence to be integrated into updated models or public health estimates, and can also support translating clinical trial results into implementation considerations. In early product development stages, population-level modelling can provide quantitative evidence linking an intervention’s minimum key performance criteria, such as efficacy or duration with its projected public health impact and benefit to communities towards meeting health targets, thus contributing to a robust evidence base 8 . While clinical evidence is essential to inform efficacy estimates and eventual registration and funding decisions for products, clinical evidence also informs model parameters, and modelling evidence in turn can improve clinical trial planning and design.…”
Section: Establishing An Iterative Approach and Framework To Generate...mentioning
confidence: 99%
“…The collaborative framework generates modelling evidence using dynamic, individual-based malaria transmission models, such as the OpenMalaria model that was developed over a period of 15 years. Detailed models are coupled with additional analytical and statistical approaches to enable rapid and computationally efficient searches of multi-dimensional parameter spaces spanning a wide range of intervention characteristics and settings 8 . Modelling the mechanisms of individual-level factors and population-level transmission dynamics links predictions of public health burden reduction to key intervention characteristics.…”
Section: Building a Collaborative Framework In Practicementioning
confidence: 99%